Multicenter prospective cohort study of the patient-reported outcome measures PRO-CTCAE and CAT EORTC QLQ-C30 in major abdominal cancer surgery (PATRONUS): a student-initiated German Medical Audit (SIGMA) Study - Mihaljevic, André Leopold; Frey, Pia-Elena; Friedrich, Mirco; Dörr-Harim, Colette; Tenckhoff, Solveig; Feißt, Manuel; Brindl, Niall; Studier-Fischer, Alexander; Kuner, Charlotte; Rahbari, Mohammad; Rahbari, Nuh Nabi; Bork, Ulrich; et al. (Annals of surgical oncology, 2021)
Background. The patient-reported outcomes (PRO) version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) and the computerized adaptive testing (CAT) version of the EORTC quality-of-life questionnaire QLQ-C30 have been proposed as new PRO measures in oncology; however, their implementation in patients undergoing cancer surgery has not yet been evaluated.